Small world: Narrow, wide, and long replication of Goyal, van der Leij and Moraga-Gonzélez (JPE 2006) and a comparison of EconLit and Scopus - Michael E. Rose (Journal of Applied Econometrics, 2021)
I undertake a narrow, wide, and long replication of Goyal, van der Leij and Moraga-Gonzélez (2006, https://doi.org/10.1086/500990). Using social network analysis, they show that the Economics profession gradually evolved into a small world. Small worlds (or small world networks) have unique information transmission capabilities. The trend is explained by the emergence of frequently publishing researchers with many distinct co-authors. In a social network, they resemble stars. The original results are robust to the usage of (I) another software, (II) a recent version of the originally used data, and (III) another database and a more sophisticated author disambiguation.
Keywords: 330; economics; social network; small world